ETHNOGENESIS AND HISTORICAL DYNAMICS OF THE QURAMA ETHNIC GROUP IN THE TASHKENT OASIS - Maftuna Abdulazizovna Ibragimova (European Science Publishing, 2024)
The article provides general and statistical information about the origin and formation history of the Qurama ethnic group living in the Tashkent oasis, Ohangaron valley, and the town of Angren from a scientific-historical perspective. Historical data were derived from the works of Uzbek, Kyrgyz, Kazakh, and Russian historians and ethnographers. Through an alternative hermeneutic method, the authors' statements were analyzed, and their conclusions are reflected in the article.
Keywords: Qurama ethnic group, Angren town, Ohangaron valley, Jungar invasion, ethnos, subethnic group, main ethnic group, meta-ethnic group, Qurama dialect, composite people, Qurama uyezd, Uzbek Quramas.